2015
DOI: 10.1074/jbc.m114.621011
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the Polarity Protein PAR3 Activates STAT3 Signaling via an Atypical Protein Kinase C (aPKC)/NF-κB/Interleukin-6 (IL-6) Axis in Mouse Mammary Cells

Abstract: Background: Loss of PAR3 triggers accelerated growth and invasion of mammary tumors via STAT3 activity. Results: PAR3 silencing induces aPKC activity, which triggers NF-B-IL-6 signaling. Conclusion: Regulation of aPKC activity is a key tumor suppressor function of PAR3. Significance: This work contributes to our understanding of mechanisms by which polarity proteins restrain tumor progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 57 publications
2
24
0
Order By: Relevance
“…Therefore, Par3 may exert its oncogenic potential through the STAT3 pathway in a subset of ovarian cancer cells that are similar to JHOC5 cells. Although at present, we have not been able to investigate the mechanism by which Par3 regulates the IL-6/STAT3 pathway, previous studies have shown that the Par3 complex has a strong relationship with the STAT3-IL-6 axis in mammalian cells [32]. Here, we provide the first indication that Par3 is associated with ovarian cancer progression through the IL-6/STAT3 pathway.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Therefore, Par3 may exert its oncogenic potential through the STAT3 pathway in a subset of ovarian cancer cells that are similar to JHOC5 cells. Although at present, we have not been able to investigate the mechanism by which Par3 regulates the IL-6/STAT3 pathway, previous studies have shown that the Par3 complex has a strong relationship with the STAT3-IL-6 axis in mammalian cells [32]. Here, we provide the first indication that Par3 is associated with ovarian cancer progression through the IL-6/STAT3 pathway.…”
Section: Discussionmentioning
confidence: 61%
“…The detailed mechanism of how Par3 is involved in tumorigenesis and invasion may depend on tumor type and is still to be elucidated. The Rac1/JNK proliferation pathway and the IL-6/STAT3 pathway may be key for understanding the functions of Par3 in promoting cancer growth [22, 25, 31, 32]. …”
Section: Introductionmentioning
confidence: 99%
“…Our novel data demonstrate strong inverted correlations among the BAY 11‐7082‐induced levels of the analysed tumour suppressors” miR‐34a, miR‐375 and miR451a, and NF‐κB‐related genes, such as RELA(p65), STAT3, TNF‐α, IL‐6 and IL‐1β, that previous studies documented as crucial mediators of inflammatory and neoplastic events in head and neck cancer35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46 (Figure 7). In line with our recent study,33 our current data suggest that NF‐κB inhibition may reverse acidic bile‐induced molecular events in normal human hypopharyngeal cells that are known to link inflammation to cancer, thereby in a sense shielding HHPC from the effects of bile‐induced oncogenic molecular events.…”
Section: Discussionmentioning
confidence: 69%
“…Of note, others have reported that Par3 inhibits NFκB activation in polarized epithelial cells by restricting aPKC activation. Thus Par3 may intersect with NFκB signaling in multiple ways (Mashukova et al , 2011; Forteza et al , 2013; Guyer and Macara, 2015). It may be important to examine the interplay between aPKC and Par3 in future studies.…”
Section: Resultsmentioning
confidence: 99%